2018
DOI: 10.1080/17571472.2018.1464731
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise prescription of primary care physician on the quality of life in patients

Abstract: PurposeThe aim of this study was to examine the effect of exercise prescribed by primary care physicians (PCPs) on the quality of life (QoL) of elderly people.MethodRandomisation was performed at PCPs level from 16 primary healthcare centers. Patients were divided into intervention and control groups. Both groups of physicians received theoretical training (14 h), and the intervention group received additional practical training on exercise prescription (10 h). Patients in the intervention group were prescribe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Twenty-three studies were selected for review. The studies, summarised in table 1, involved: 6 trials [28][29][30][31][32][33] ; 13 observational [34][35][36][37][38][39][40][41][42][43][44][45][46] ; 3 qualitative [47][48][49] ; and 1 mixed methods. 50 Studies originated in eight different regions: 7 from Canada 28 30 31 38 43 44 50 ; 7 from Sweden 34 35 41 42 46 48 49 ; 2 from New Zealand 36 47 ; 2 from the UK 32 33 ; 2 from France 37 39 ; 1 each from the USA 29 and Australia 45 and a single study from 12 Latin-American countries.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-three studies were selected for review. The studies, summarised in table 1, involved: 6 trials [28][29][30][31][32][33] ; 13 observational [34][35][36][37][38][39][40][41][42][43][44][45][46] ; 3 qualitative [47][48][49] ; and 1 mixed methods. 50 Studies originated in eight different regions: 7 from Canada 28 30 31 38 43 44 50 ; 7 from Sweden 34 35 41 42 46 48 49 ; 2 from New Zealand 36 47 ; 2 from the UK 32 33 ; 2 from France 37 39 ; 1 each from the USA 29 and Australia 45 and a single study from 12 Latin-American countries.…”
Section: Resultsmentioning
confidence: 99%
“…48 Another qualitative study of GPs, conducted in New Zealand, using one-to-one interviews, found a much more enthusiastic attitude towards EP. 47 The main barrier reported was time, and the support of an exercise professional with the expertise and protected time 37 Lack of time 37 Perceived barriers to prescribing 39 Training, eg, workshop and validated tools 33 37 38 40 43 44 EP materials and training packs for patients 33 Patient Physically inactive at baseline 34 Seasonality and weather 50 Medical conditions 50 Lack of purpose after the study ended 50 Lack of clarity on the purpose of the EP and what is expected of them specifically 49 Education and messaging from family physician 50 Prevalence of comorbidity 45 Higher levels of self-efficacy and confidence in one's readiness to change; lower BMI and lower baseline PA levels and those who had self-reported better health were more likely to attain improvements in PA levels 46…”
Section: Patient Factorsmentioning
confidence: 99%
See 3 more Smart Citations